Examining the Permeation of Toxic Chemicals Through Barrier Materials - Bicket, Alex (Université d'Ottawa | University of Ottawa, 2025)
The wide usage and availability of hazardous substances in many facets of todays life necessitate people must be in close proximity to, and risk contact with, hazardous chemicals during the conduct of their work. One layer of risk mitigation for exposure to hazardous substances is the use of protective equipment. In the case of hazardous chemicals, this is often a polymer layer worn to balance protection with mobility. However, modelling of the diffusion of chemicals through rubbery polymers is difficult and common test methods may contain sources of error inherent in the experimental design. Through numerical simulations, this thesis examines the accuracy of current standard test methods, seeks to determine which factors have the most impact on errors and suggests mitigations. Experiments were conducted to examine the permeation and determine transfer properties using the time-lag method. This work suggests that some common testing protocols have sources of error inherent to the design and experimental conditions must be carefully considered when selecting test protocols.
Keywords: Permeation; Membrane; Diffusion; Simulation